Sistem Pendukung Keputusan Pemilihan Calon Ketua Komite Sekolah Menggunakan Metode CoCoSo - Bilatasya, Yolanda; Juledi, Angga Putra; Irmayani, Deci; Harahap, Syaiful Zuhri (Building of Informatics, Technology and Science (BITS), 2025)
The election of the school committee chairperson is one of the important decision-making processes that directly impacts the sustainability and effectiveness of collaboration between the school and parents/guardians. At SMP Negeri 1 Rantau Selatan, the selection process for the committee chairperson has been conventional, subjective, and lacks a structured and standardised assessment system. This results in the selection process being based on popularity and personal connections rather than objective competence and qualifications. To address this issue, this study aims to design and implement a Decision Support System (DSS) based on the Combined Compromise Solution (CoCoSo) method, which can accommodate various quantitative evaluation criteria and generate more objective, transparent, and accountable decision recommendations. The CoCoSo method was chosen for its ability to integrate a compromise approach to conflicting criteria and produce consistent alternative rankings through three aggregation techniques: arithmetic mean, relative sum, and compromise programming. This study uses five main criteria to assess the suitability of committee chair candidates: experience in the field of education, communication skills, leadership, understanding of education policy, and integrity. Data was obtained from 15 committee chair candidates based on observation and questionnaire results, which were then processed through the CoCoSo method stages, including decision matrix formation, value normalisation, positive and negative ideal solution calculations, and final score aggregation. The data processing results show that the candidate named Eko Prasetyo obtained the highest compromise value in all CoCoSo calculation approaches with a final Ki value of 2.505, consistently placing him as the top-ranked candidate in the system's recommendations. This demonstrates that the CoCoSo method is effective in evaluating and determining the best candidate based on a data-driven and scientifically rational approach. Additionally, the system built can also serve as a strategic tool to enhance the quality of participatory educational governance at the school unit level.